Role of early experience in the development of preference for low-quality food in sheep - Catanese, Francisco Hernan (2010)
Domestic ruminant selectivity induces floristic changes in pasturelands, risking sustainability and limiting the subsequent availability of susceptible plant species. Development of preferences for species of lower nutritional quality may help to overcome those problems. In this study, we tested the hypothesis that early experience of sheep with a low-quality food (LQF) in a nutritional enriched context increases preference for LQF in adulthood. We predicted a higher proportional consumption of LQF in experienced lambs (EL) than in inexperienced lambs (IL) in choice situations involving LQF and alternative foods. Additionally, we determined intake of LQF by EL and IL at different levels of high-quality food (HQF) availability. From 60 to 210 days of age, EL were fed in separated feed bunks mature oat hay (LQF) simultaneously with sunflower meal (SM) and corn grain (CG), whereas IL were fed alfalfa hay (HQF) simultaneously with SM and CG. After exposure, EL and IL were offered LQF in free choice situations involving alternative foods, and also at five levels of HQF availability (100%, 75%, 50%, 25% and 0% of ad libitum intake). Proportional consumption of LQF was lower or similar in EL than IL. Intake of LQF was also lower or similar in EL than IL at all levels of HQF availability, except when the LQF was the only food available. Our results did not support the hypothesis that early experience with a LQF in a nutritional enriched context increases preference for LQF in adulthood. On the contrary, experience with LQF diminished subsequent preference for LQF in adulthood. It is proposed that, in the conditions of our study, continuous comparison between the LQF and the high-quality supplements (CG and SM) during the early exposure period lead to devaluation of LQF by EL through a simultaneous negative contrast effect.